Cyber socializing and victimization of women - Halder Debarati; Jaishankar Karuppannan (Temida, 2009)
Web 2.01 has redefined the virtual life of ordinary individuals and has given wide opportunities to internet users including women to exchange ideas, interact with like minded people and participate in the development of virtual societies as per one's own choices. Social networking websites (SNWs), a segment of Web 2.0 is very popular among the internet users. However, there is a dark side of these SNW's too. They have become havens for offenders to victimize women, the most vulnerable targets in the internet, after children. In this paper, we examine the victimization of women in the social networking websites in general, analyze the trends of such victimization from socio - legal - victimological angle and ascertain the reasons for the growth of such victimization.